2.8 V Aqueous Lead Dioxide–Zinc Rechargeable Battery Using H2SO4–K2SO4–KOH Three Electrolytes. Issue 2 (3rd February 2020) - Gao, Tong; Sun, Yu; Gong, Liangyu; Ma, Chuanli; Wang, Jie; Su, Linghao
Abstract : Aqueous chargeable batteries always suffer from narrow voltage window due to water electrolysis. In this paper, a high-voltage aqueous lead dioxide–zinc battery is constructed by designing negative and positive materials in alkaline and acidic electrolytes, respectively. It not only exhibits an open circuit voltage of 2.8 V and a discharge voltage of 2.75 V, which is the highest among PbO2 -based aqueous batteries, but also provides a promising strategy to obtain high operating voltage without using expensive organic electrolytes or solid electrolyte separator.